Prevalence of general and abdominal obesity in Portugal: comprehensive results from the National Food, nutrition and physical activity survey 2015-2016 - Oliveira, Andreia (2018)
Collaborators: Lopes C, Oliveira A, Severo M, Torres D, Rodrigues S, Ramos E, Vilela S, Guiomar S, Oliveira L, Alarcão V, Nicola P, Mota J, Teixeira P, Soares S, Andersen LF. IAN-AF Consortium - investigadores - Sofia Guiomar (Instituto Nacional de Saúde Doutor Ricardo Jorge)